Flow cytometry identifies an early stage of platelet apoptosis produced by agonists of the P2X1 and P2X7 receptors. (19th May 2022) - Wong, Joelyn; Gu, Ben J.; Teoh, Harry; Krupa, Malgorzata; Monif, Mastura; Slee, Mark; Wiley, James S.
Abstract: Platelets express P2X1 receptors and our data also show the expression of P2X7 receptors. We studied the role of both receptors in platelet apoptosis by incubation of PRP with P2X agonists, then centrifuged to remove viable platelets, and analyzed the supernatant by flow cytometry to identify a sparse platelet-derived population that stained with MitoTracker dyes and CD41. BzATP, a potent agonist of P2X receptors, and ABT737, an activator of intrinsic apoptosis, produced altered platelets that stained moderately for annexin V and corresponded to an early stage apoptotic platelet (ESAP). Over a range of BzATP concentrations, we observed a dose-dependent formation of ESAPs between 5 and 500 uM BzATP, together with a variable formation of ESAPs at nanomolar ATP or BzATP (50–200 nM). Production of ESAPs occurred with αβ-meATP, while responses with either BzATP or αβ-meATP showed desensitization at a higher agonist concentration. Formation of ESAPs by either 100 nM or 0.5 mM BzATP was inhibited by preincubation of platelets with latrunculin A, an inhibitor of the actin cytoskeleton that prevents apoptosis. ESAP production was totally inhibited by preincubation of platelets with methyl-beta-cyclodextrin, which removes cholesterol from lipid rafts. Our data show that both P2X1 and P2X7 receptors are localized in platelet lipid rafts where P2X-agonists act to produce early stage apoptotic platelets.